How can aerial imagery and vegetation indices algorithm can be used for monitoring crop through geotagged system? A review - Kumaran, Vikneswaran Jeya; Mohidem, Nur Adibah; Che’ya, Nik Norasma; Wan Ilahi, Wan Fazilah; Arif Shah, Jasmin; Yusof, Norhakim (HH Publisher, 2023)
As the world population grows, it is crucial that food production is linearly proportional to the growing demands of food across the globe. The agriculture sector has many opportunities as well as challenges in the upcoming years. Many innovations have been achieved in the previous years and there are more technologies being researched annually. To automize agriculture, unmanned aerial vehicles (UAV) are extensively being studied to be applied in agriculture. This technology is being explored by integrating it with other sciences as well such as vegetation indices. Vegetation indices allow extensive analysis to be done on the images taken through the UAV. Currently, there are many studies that are done to monitor crops using information obtained from vegetation indices derived from aerial imagery. The crops that are monitored are also geotagged so that precise information can be extracted. This paper will be assessing the usage of aerial imagery, vegetation indices as well as geotagging to monitor crops.